Epidermolysis bullosa: Advances in research and treatment. Issue 10 (8th August 2019) - Prodinger, Christine; Reichelt, Julia; Bauer, Johann W.; Laimer, Martin
Abstract: Epidermolysis bullosa (EB) is the umbrella term for a group of rare inherited skin fragility disorders caused by mutations in at least 20 different genes. There is no cure for any of the subtypes of EB resulting from different mutations, and current therapy only focuses on the management of wounds and pain. Novel effective therapeutic approaches are therefore urgently required. Strategies include gene‐, protein‐ and cell‐based therapies. This review discusses molecular procedures currently under investigation at the EB House Austria, a designated Centre of Expertise implemented in the European Reference Network for Rare and Undiagnosed Skin Diseases. Current clinical research activities at the EB House Austria include newly developed candidate substances that have emerged out of our translational research initiatives as well as already commercially available medications that are applied in off‐licensed indications. Squamous cell carcinoma is the major cause of death in severe forms of EB. We are evaluating immunotherapy using an anti‐PD1 monoclonal antibody as a palliative treatment option for locally advanced or metastatic squamous cell carcinoma of the skin unresponsive to previous systemic therapy. In addition, we are evaluating topical calcipotriol and topical diacerein as potential agents to improve the healing of skin wounds in EBS patients. Finally, the review will highlight the recent advancements of gene therapy development for EB.